O fomento ao empreendedorismo e à economia criativa na cidade do recife: um estudo de caso sobre o Porto Digital. - Mendes, Ricardo Verçoza (2020)
This dissertation is situated in the field of studies of entrepreneurship, creative economy and clusters. The research will be guided by the following research problem: what factors and conditions contributed to the emergence of Porto Digital? From the definitions of the respective fields of study present in the dissertation, will occur the analysis of the genesis of Porto Digital, ascertaining the factors and conditioning factors that contributed and converged to its emergence and development. Thus, the methodological design will seek, through an explanatory and documentary investigation, strengthened by a qualitative approach - using the case study method -, to gather information necessary for the understanding of Porto Digital as a cluster and technological park, as well as to outline its contributions to the promotion of the creative economy in Pernambuco. The research findings suggest that Porto Digital emerged from a context of constant technological evolution, the interaction between companies, government and university (Triple Helix) and the establishment of public policies. This paper is intended to promote this study in order to advance the debate on clusters and technology parks in the midst of a constantly changing economy.